Civil Law Protection for Consumers Against Contractual Default in Illegal Fintech-Based Online Lending Practices: Implications for Family Economic Resilience - Risdiana; Mirza Amelia (Universitas Islam Negeri Raden Intan Lampung, 2025)
Illegal online lending fintech has created civil law problems that extend beyond individual consumer losses and threaten family economic resilience. This article aims to analyze the construction of default and defective agreements in illegal online lending, examine civil legal protection for injured consumers, and formulate a protection model responsive to household vulnerability. This normative legal research employs statutory, conceptual, case-based, and limited comparative approaches. The data sources consist of primary legal materials, including the Civil Code, Consumer Protection Law, EIT Law, Personal Data Protection Law, OJK regulations, and DSN-MUI fatwa, supported by secondary materials from journals, books, and institutional reports. The analysis is guided by civil liability theory, consumer protection theory, personal data protection, family economic resilience, and Islamic fairness in muamalah. The findings show that illegal lending may involve default, defective consent, unfair clauses, unlawful acts, and personal data misuse. Policy reform should integrate civil remedies, data recovery, digital supervision, family financial literacy, and coordinated enforcement.